Geologi Daerah Talumolo dan sekitarnya, Kecamatan Dumbo Raya, Provinsi Gorontalo - Alief Ardiansyah; Sri Maryati; Noviar Akase (Universitas Negeri Gorontalo, 2026)
This research is located in Talumolo Village and its surroundings in Dumbo Raya District, Gorontalo City, Gorontalo Province, which is located at coordinates 0°32'59